STATUS DAN PENGEMBALIAN MASKAWIN SETELAH PERCERAIAN DALAM PERSPEKTIF GENDER - Toto Supriyanto Supriyanto (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2021)
This article discusses dowry status and return of dowry after divorce from a gender perspective. The background is ambiguity in the transaction status and the wife's ownership status of the dowry, which implies that there is a provision for returning the dowry that has been given by the husband or withholding the dowry that has not been given but has been promised in the marriage contract. The provision for the return of the dowry was allegedly against the principles of gender equality. By using the literature survey method this article was carried out. This article finds evidence of ambiguity in the transactional status of dowry in Islamic law between grants: selfless gifts or ijarah: rewards for the pleasures that the wife gives to her husband. There is also evidence that the wife's ownership status of the dowry is not clear, whether it is absolute property, or non-absolute ownership because it depends on the behavior of the wife in carrying out her role as a wife, whether she is obedient or rebellious. After being analyzed using gender principles in the form of 14 basic rights and five types of indicators of gender inequality, it was found that the dowry status for wives is not gender equal in the form of discrimination and subordination. Provisions for returning the dowry either in half or in full because there has been no sexual intercourse between husband and wife is classified as subordination and marginalization; as well as the return of dowry due to divorce with khulu 'and fascikh, including discrimination and stereotypes